Responding to global stimulant use: challenges and opportunities. Issue 10209 (2nd November 2019) - Farrell, Michael; Martin, Natasha K; Stockings, Emily; Bórquez, Annick; Cepeda, Javier A; Degenhardt, Louisa; Ali, Robert; Tran, Lucy Thi; Rehm, Jürgen; Torrens, Marta; Shoptaw, Steve; McKetin, Rebecca
Summary: We did a global review to synthesise data on the prevalence, harms, and interventions for stimulant use, focusing specifically on the use of cocaine and amphetamines. Modelling estimated the effect of cocaine and amphetamine use on mortality, suicidality, and blood borne virus incidence. The estimated global prevalence of cocaine use was 0·4% and amphetamine use was 0·7%, with dependence affecting 16% of people who used cocaine and 11% of those who used amphetamine. Stimulant use was associated with elevated mortality, increased incidence of HIV and hepatitis C infection, poor mental health (suicidality, psychosis, depression, and violence), and increased risk of cardiovascular events. No effective pharmacotherapies are available that reduce stimulant use, and the available psychosocial interventions (except for contingency management) had a weak overall effect. Generic approaches can address mental health and blood borne virus infection risk if better tailored to mitigate the harms associated with stimulant use. Substantial and sustained investment is needed to develop more effective interventions to reduce stimulant use.